The Rhodesian security forces, mujibhas and chimbwidos in the liberation struggle of Zimbabwe (1960-1980) - Mutanga, Sharleene T. (Midlands State University, 2018)
The study explores the plight of mujibas and chimbwidos who were guerrilla aides in the liberation struggle for Zimbabwe. That is to say the horrific experiences they encountered during the war and bringing out their untold stories. It contributes to the historiography of the Zimbabwean liberation struggle by focusing on the effects of violence on the mujibas and chimbwidos. The war which took place between ZANU and ZAPU against the Rhodesian Security Forces from the period of 1960 until they acquired independence in 1980, saw the evolution of mujibas and chimbwidos idea. The study unmasks the horrible and gory experiences they went through whilst they were providing the guerrillas with food and information about the security forces. Also the harsh punishments they received after being caught by the security forces and beatings they got from crossing the guerrillas .The study brings out the physical and psychological effects of violence on them and other humanitarian crisis they faced during the war. The study demonstrates that mujibas and chimbwidos needs to be appreciated in the history of the liberation struggle because their position was risky, they were caught in the middle of pressure from both armies as they used violence and coercion. They were exposed to sexual violence, diseases and hunger whilst living under horrible conditions in the bushes and the Keeps they were forced into. This study is constructed on wide oral testimonies of former mujibas and chimbwidos, secondary sources and primary sources. It breaks the silence of the untold stories of the horrific experiences of mujibas and chimbwidos.